The Interplay of Support, Engagement, and Motivation: Mediation by Academic and Emotional Resources - On Chee Hoong (Journal of Advanced Research in Social Sciences and Humanities, 2025)
Aim: The study aims to investigate the causal relationships between students’ learning engagement, impact on motivation for learning, among undergraduate students in higher education institutions. Drawing on self determination theory through moderating the impact of learning persistence, as well as the mediating role of academic and emotional support study aims to bridge theoretical and empirical research gaps.Methodology: An online research survey through the use of Google form was conducted to collect data from 430 undergraduate students in Malaysian higher education institutions. Structural equation modelling to analyze the data. The convergent validity, discriminant validity, and hypotheses testing of the model were performed using SmartPLS 4 statistical software.Findings: The findings show that students’ learning engagement has a direct impact on academic and emotional support. Also, the significant mediating role of academic and emotional support among students in learning engagement and motivation for learning. A significant moderating role of learning persistence on academic and emotional support and motivation for learning.Implications/Novel Contribution: The results have important theoretical implications by complicating the persistence construct and making applied recommendations for design and delivery to foster sustained, effective, and motivated engagement in global E-learning environments. According to SDT, it is important that university instructors be prepared to deliver both academic support and emotional support that maximizes students’ motivation for learning. Future research directions are suggested.